Characteristics of non-exercise activity thermogenesis in male collegiate athletes under real-life conditions - Goshozono, Mika; Miura, Nozomi; Torii, Suguru; Taguchi, Motoko (Frontiers in Sports and Active Living, 2024)
Athletes experience large total energy expenditure; therefore, it is important to clarify the characteristics of the components of total energy expenditure. To date, few studies have examined particularly the volume and activity intensity of non-exercise activity thermogenesis (NEAT) in athletes in comparison with non-athletes under real-life conditions. This study aimed to determine the volume and intensity of NEAT in collegiate athletes. Highly trained Japanese male collegiate athletes (n = 21) and healthy sedentary male students (n = 12) participated in this study. All measurements were obtained during the athletes' regular training season under real-life conditions. NEAT was calculated using metabolic equivalent (MET) data using an accelerometer. The participants were asked to wear a validated tri-axial accelerometer for seven consecutive days. Physical activity intensity in NEAT was classified into sedentary-(1.0-1.5 METs), light-(1.6-2.9 METs), moderate-(3.0-5.9 METs), and vigorous-intensity (≥ 6 METs). NEAT was significantly higher in athletes than in non-athletes (821 ± 185 kcal/day vs. 643 ± 164 kcal/day, p = 0.009). Although there was no significant difference in NEAT values relative to body weight (BW) between the groups (athletes: 10.5 ± 1.7 kcal/kg BW/day, non-athletes: 10.4 ± 2.2 kcal/kg BW/day, p = 0.939), NEAT to BW per hour was significantly higher in athletes than in non-athletes (0.81 ± 0.16 kcal/kg BW/h vs. 0.66 ± 0.12 kcal/kg BW/h, p = 0.013). Athletes spent less time in sedentary- and light-intensity activities and more time in vigorous-intensity activities than non-athletes (p < 0.001, p = 0.019, and p = 0.030, respectively). Athletes expended more energy on vigorous- and moderate-intensity activities than non-athletes (p = 0.009 and p = 0.011, respectively). This study suggests that athletes' NEAT relative to BW per day is similar to that of non-athletes, but athletes spend less time on NEAT, which makes them more active in their daily lives when not exercise and sleep.